Hydrobiological and Geochemical Responses to Trout Cage Aquaculture in Lake Ecosystem - Artem Lapenkov; Alina Guzeva; Ksenia Zaripova; Dina Dudakova; Artem Trifonov (Limnological Review, 2024)
This study investigates the seasonal dynamics and interrelationships between geochemical and hydrobiological parameters in lake ecosystems impacted by fish cage farming in Lake Ladoga, Russia. Environmental conditions at three trout farms were assessed, focusing on water and sediment quality as well as benthic and zooplankton communities. For each farm, two categories of sampling sites were designated: cage sites and reference sites located 100–600 m away from the cages. Fieldwork was carried out across four seasons in 2023: February, June, August, and November. The findings indicate that intensive fish feeding results in significant organic waste accumulation beneath trout cages, altering the composition and abundance of planktonic and benthic organisms. The organic matter content in sediments beneath the cages during periods of intensive feeding was found to increase 2–5 times compared to the reference sites. In winter, accumulated organic matter in the sediments underwent mineralization, bringing hydrobiological indicators closer to the reference values. The geochemical and hydrobiological parameters analyzed in this study serve as valuable indicators for developing ecological monitoring approaches in freshwater cage aquaculture.